2011
DOI: 10.1038/cr.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for site-specific reading of unmodified R2 of histone H3 tail by UHRF1 PHD finger

Abstract: We report two NMR complex structures of PHD UHRF1 binding to unmodified or K9 trimethylated histone tails, which clarify a controversy regarding how the binding of UHRF1 to H3 tails is mediated. Based on our structures, H3R2, not H3K9, mediates PHD binding.Human UHRF1, also known as ICBP90, plays central roles in maintaining CpG DNA methylation [1,2] and epigenetic code inheritance [3]. It harbors five recognizable functional domains: an ubiquitin-like domain (UBL) at the N-terminus, a tandem tudor domain (Tud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 13 publications
(47 reference statements)
9
65
1
Order By: Relevance
“…1A). In agreement with previous reports (19,20,23,25), our binding assay using isothermal titration calorimetry (ITC) showed that isolated TTD and PHD bound to the N-terminal H3 peptide depending on K9me3 and unmodified R2, respectively (Table 1 and SI Appendix, SI Results). We also observed 1:1 stoichiometric binding of TTD-PHD to the H3 tail bearing unmodified R2 and K9me3 with significantly higher affinity (K d = 0.37 μM) compared with TTD (K d = 1.75 μM) or PHD finger (K d = 1.47 μM) alone (Table 1 and SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…1A). In agreement with previous reports (19,20,23,25), our binding assay using isothermal titration calorimetry (ITC) showed that isolated TTD and PHD bound to the N-terminal H3 peptide depending on K9me3 and unmodified R2, respectively (Table 1 and SI Appendix, SI Results). We also observed 1:1 stoichiometric binding of TTD-PHD to the H3 tail bearing unmodified R2 and K9me3 with significantly higher affinity (K d = 0.37 μM) compared with TTD (K d = 1.75 μM) or PHD finger (K d = 1.47 μM) alone (Table 1 and SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 78%
“…Trimethylation of histone H3K9 is well known to be associated with transcriptional suppression (31), but the role of H3-R2 methylation has just started to be unveiled (32)(33)(34)(35). Recently, H3-R2 binding of UHRF1 was shown to be dispensable for localization of UHRF1 at pericentromeric heterochromatin (19,20). However, the biological relevance of the histone code (H3-R2me0-K9me3) that is recognized by the TTD-PHD of UHRF1 remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations